Kinetic Study of the CO2 Reforming of CH4 to Synthesis Gas Over Carbonaceous Catalyst - Guo, Fengbo; Zhang, Yongfa (Asian Journal of Chemistry, 2011)
The CO2 reforming of CH4 over carbonaceous catalyst was performed in a plug flow reactor (PFR) at temperatures range from 1223-1323 K, the ratio of CH4/CO2 = 1 and residence time 3-30 s under normal pressure. The outlet gas was analyzed by gas chromatogram (GC-960TCD and GC-950TCD), the carbonaceous catalyst was analyzed with element analyzer and specific surface area analyzer. The experimental results show that the conversion of CH4 and CO2 increases with the increase of the reaction temperature and residence time, but the conversion of CO2 was significantly higher than the conversion of CH4 at the same reaction condition, which indicate that the gasification reaction of the carbonaceous catalyst and carbon dioxide was occurred during the reforming process. At 1323 K and residence time over 20 s, the conversion of CH4 and CO2 can be expected over 90 %. The carbonaceous catalyst is a highly promising catalyst for the CO2 reforming of CH4 to synthesis gas. The kinetics of the CO2 reforming of CH4 on carbonaceous catalyst was described in a rate law, which the experimental data was analyzed in non-linear regression. The apparent activation energy Ea and the pre-exponential factor A were solved. A comparison is made between calculation data and experimental data of the CH4 conversion, which illustrates the rationality of the kinetic model.